Hubungan Lagu Berbahasa Arab dengan Maharah Istima’ Mahasiswa - Nurul Fawzani; Firdaus; Akmal (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2022)
The purpose of this study was to determine the degree of relationship between Arabic songs and maharah istima' (listening ability) of the Students of Arabic Education Study Program IAI Muhammadiyah Sinjai. This research belongs to the type of correlational research and uses a quantitative approach. The object of this research is the Arabic Language Education Study Program students, totaling 86 people, with a total sample of 68 people. The results of this study indicate that there is a relationship between Arabic songs and maharah istima' of the Students of Arabic Education Study Program IAI Muhammadiyah Sinjai. Based on the product moment correlation test results obtained a value of 0.000 <0.05 so that H0 is rejected and Ha is accepted. In the coefficient interval 0.60-0.799, the results of the correlation coefficient of 0.722 indicate that the correlation between Arabic songs and maharah istima' is included in the strong category.